Risk Based Inspection using API RP 580 and DNV RP F116 Towards Free Spanning Pipelines - Iftinaniffah Qonitah; Yoyok Setyo Hadiwidodo; Daniel Mohammad Rosyid (International Journal of Offshore and Coastal Engineering (IJOCE), 2021)
The free span that occurs in the subsea pipeline can cause fatigue due to vortex induced vibration and local buckling. From the risk of failure that may occur, a risk-based inspection scheduling required. The 14" Underwater pipe belongs to PT. The X located in the Madura Strait is used to transmit gas from the CPP to ORF with a length of 65 km which has 554 free spans. In scheduling inspections, the commonly used codes are API RP 580 and DNV RP F116. This journal will discuss the difference between these two codes. Reliability calculations use Monte Carlo simulation with VIV failure mode and local buckling failure mode. The consequences of failure are reviewed on safety, environmental and asset aspects. API RP 580, shows the environmental aspect and the safety aspect of both modes of failure has the next inspection in 6 years, while the asset aspect is 3 years. At DNV RP F116, scheduling inspection of safety aspect on both modes is 3 years and environmental aspects is a year later, while the asset aspect would be better to change the pipe